Literasi Hukum Digital Dan Kesehatan Mental Siswa Dalam Perspektif Hukum Pidana, Perdata, Dan Kesehatan Di SMP Al-Ikram Medan - Etty Uyun; Mhd. Ihwanuddin Hasibuan; Ardina Fariani Lubis; Helviana Hasibuan; Bagus Firman Wibowo (STIKES Columbia Asia Medan, 2026)
This community service activity aims to improve students' digital legal literacy and awareness of mental health from the perspectives of criminal law, civil law, and health law at SMP Al-Ikram Medan. The background of this program is the increasing use of digital media among students which raises legal risks such as cyberbullying, online fraud, privacy violations, and their impacts on students’ mental health. The method used includes legal education, interactive counseling, group discussions, and evaluation through pre-test and post-test. The results show an increase in students’ understanding of digital legal risks, students’ rights and obligations in cyberspace, and awareness of mental health protection. This program contributes to strengthening preventive legal culture and early mental health protection among students.